1998
DOI: 10.1541/ieejfms1990.118.2_169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the degradation of ZnO varistor with various additives

Abstract: We have evaluated the electrical degradation of the Zincoxide(ZnO) varistors added two kinds of additives by the V-I measurements and the improved ICTS method. Results of the V-I characteristics show that both the characteristics of varistors added Bi2O3 and CoO and those added Bi2O3 and MnO2 were recovered by thermal annealing. This indicates that the distribution of O2-ion changed by applying voltage was returned to the initial condition by thermal annealing. Results of the improved ICTS measurement show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…21) The relationship between the change in the interface state and the deformation of DSB caused by degradation is most important in understanding the degradation mechanism of ZnO varistors. However, to date, there are no reports on the experimental characterization of the change in distribution of the interface states caused by degradation.…”
Section: Introductionmentioning
confidence: 99%
“…21) The relationship between the change in the interface state and the deformation of DSB caused by degradation is most important in understanding the degradation mechanism of ZnO varistors. However, to date, there are no reports on the experimental characterization of the change in distribution of the interface states caused by degradation.…”
Section: Introductionmentioning
confidence: 99%
“…12), 14) These results suggest that trend of increase and decrease on I r with respect to time is partially affected by Co distribution in the SRZVC.…”
Section: Apparent Density and V Bmentioning
confidence: 72%
“…Moreover, it is reported that one of the mechanism of the electrical degradation is due to the diffusion of oxygen ions through the grain boundary caused by application of bias voltage and then double Schottky barriers are distorted by the re-distribution of electrons and holes near the grain boundary (1) (2) . In this study, the relationship between electrical degradation and the orientation of ZnO grains of Sb 2 O 3 -added ZnO varistors are discussed.…”
Section: Figmentioning
confidence: 99%